The Yiddish policemen's union novel /c - Chabon, Michael (1963-....). (New York : HarperCollins Publishers, 2007)
In a world in which Alaska, rather than Israel, has become the homeland for the Jews following World War II, Detective Meyer Landsman and his half-Tlingit partner Berko investigate the death of a heroin-addled chess prodigy
Hugo Award for Best Novel, 2008
Nebula Award for Best Novel, 2007
Keywords: Jews -- Fiction; Murder -- Investigation -- Fiction; Alaska -- Fiction